A new tool to test active ingredient using lactic acid in vitro, a help to understand cellular mechanism involved in stinging test: An example using a bacterial polysaccharide (Fucogel®). Issue 3 (7th February 2018) - Sakka, Mehdi; Leschiera, Raphael; Le Gall‐Ianotto, Christelle; Gouin, Olivier; L'herondelle, Killian; Buscaglia, Paul; Mignen, Olivier; Philbé, Jean‐Luc; Saguet, Thibaut; Carré, Jean‐Luc; Misery, Laurent; Lebonvallet, Nicolas
Abstract: The stinging test is an in vivo protocol that evaluates sensitive skin using lactic acid (LA). A soothing sensation of cosmetics or ingredients can be also appreciated through a decrease in stinging score. To predict the soothing sensation of a product before in vivo testing, we developed a model based on an LA test and substance P (SP) release using a co‐culture of human keratinocytes and NGF‐differentiated PC12 cells. A bacterial fucose‐rich polysaccharide present in Fucogel ® was evaluated as the soothing molecule in the in vivo stinging test and our in vitro model. Excluding toxic concentrations, the release of SP was significant from 0.2% of lactic acid for the PC12 cells and from 0.1% of lactic acid for the keratinocytes. When the pH was adjusted to approximately 7.4, LA did not provoke SP release. At these concentrations of LA, 0.1% of polysaccharide showed a significant decrease in SP release from the two cellular types and in co‐cultures without modifying the pH of the medium. In vivo, a stinging test using the polysaccharide showed a 30% decrease in prickling intensity vs the placebo in 19 women between the ages of 21 and 69. Our in vitro model is ethically interesting and is adapted for cosmetic ingredients screening because it does not use animal experimentation and limits human volunteers. Moreover, Fucogel ® reduced prickling sensation as revealed by the in vivo stinging test and inhibits the neurogenic inflammation as showed by our new in vitro stinging test based on SP release.